La mort sobtada de Joan I a la llum d'uns exemples d'Eiximenis. - RENEDO, XAVIER (Scripta)
Analysis of the theology of sudden death in the late Middle Ages, taking as a point of reference several religious and moral texts and some accounts of the «mors repentina et improvisa» of John I, King of Aragon (19/05/1396). At the same time, are also analyzed exempla from various works by Francesc Eiximenis (circa 1330-1409), from the Dotzè del Crestià (1387) to the Vita Christi (1403), which have as protagonists kings who are punished by divine providence for their terrible management of public affairs.